Are movement-based mindful exercises (QIGONG, TAI CHI, AND YOGA) beneficial for stroke and Parkinson's disease? A scoping review - Cristina García-Muñoz; Paula González-García; María Jesús Casuso-Holgado; Javier Martínez-Calderón; Alberto Marcos Heredia-Rizo (Elsevier, 2023)
Objective: To synthesize evidence from systematic reviews on the effects of qigong, tai chi, and yoga in people with neurological diseases. Methods: A systematic search was conducted in PubMed, PsycINFO, Embase, CINAHL and Cochrane Library until September 2022. Methodological quality was assessed using the AMSTAR 2 tool. A qualitative synthesis of included reviews and meta-analyses was performed. Citation matrices and the corrected covered area were used to explore the overlap of randomized controlled trials among reviews. Results: Nineteen systematic reviews (containing 74 trials and 80 meta-analyses) in people with Parkinson's disease (PD) or stroke were included. The critical domains of the AMSTAR 2 were not satisfied in more than half of the reviews, and only 4 evaluated the certainty of the evidence. The overlap was very high (21.7%) and high (11%) for tai chi studies in PD and stroke, respectively. In people with PD, qigong, yoga, and tai chi can improve balance, with tai chi being beneficial to increase functional mobility. For stroke patients, tai chi was better than controls to enhance motor function and independence, but not for health-related quality of life and quality of sleep. Findings on balance, walking ability and depression were inconclusive in stroke population. Conclusions: Qigong, tai chi, and yoga appear to be effective to improve balance performance in people with PD. Tai chi practice enhances motor function and independency in stroke patients.